Smad3 Prevents β-Catenin Degradation and Facilitates β-Catenin Nuclear Translocation in Chondrocytes - Zhang, Ming (American Society for Biochemistry and Molecular Biology, 2010)
Our previous study demonstrated that transforming growth factor (TGF)-β activates β-catenin signaling through Smad3 interaction with β-catenin in chondrocytes. In the present studies, we further investigated the detailed molecular mechanism of the cross-talk between TGF-β/Smad3 and Wnt/β-catenin signaling pathways. We found that C-terminal Smad3 interacted with both the N-terminal region and the middle region of β-catenin protein in a TGF-β-dependent manner. Both Smad3 and Smad4 were required for the interaction with β-catenin and protected β-catenin from an ubiquitin-proteasome-dependent degradation. In addition, the formation of the Smad3-Smad4-β-catenin protein complex also mediated β-catenin nuclear translocation. This Smad3-mediated regulatory mechanism of β-catenin protein stability enhanced the activity of β-catenin to activate downstream target genes during chondrogenesis. Our findings demonstrate a novel mechanism between TGF-β and Wnt/β-catenin signaling pathways during chondrocyte development.